2019
DOI: 10.1071/pc18018
|View full text |Cite
|
Sign up to set email alerts
|

What to call a dog? A review of the common names for Australian free-ranging dogs

Abstract: Wildlife research is informed by human values and interests, and these are reflected in, and reinforced by, the language used to describe particular species and animals. Examining factors that influence the use of common names of contentious taxa such free-ranging dogs is important, as naming can influence the design and reception of scientific studies. There are a range of common names for free-ranging dogs in Australian scientific literature but the most common names are ‘dingoes’ and ‘wild dogs’. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…As the diversity in common and scientific names suggests, the taxonomic identity and status of the Australian dingo has been unsettled and controversial since its initial description in 1792 (Jackson et al 2017;Smith et al 2019), and the name(s) selected by authors can act as a reliable indicator of the subject matter (e.g. 'wild dogs' in reference to livestock management and 'dingoes' in reference to ecological roles and conservation) and even the employment and funding sources of authors (Kreplins et al 2018). Although a lack of scientific consensus persists on what makes a dingo a dingo, and, indeed, whether it matters, here, for simplicity, we consider all wild-living dogs as a single group in Australia (including dingoes, feral dogs and their hybrids), and refer to them hereafter as dingoes, unless stated otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…As the diversity in common and scientific names suggests, the taxonomic identity and status of the Australian dingo has been unsettled and controversial since its initial description in 1792 (Jackson et al 2017;Smith et al 2019), and the name(s) selected by authors can act as a reliable indicator of the subject matter (e.g. 'wild dogs' in reference to livestock management and 'dingoes' in reference to ecological roles and conservation) and even the employment and funding sources of authors (Kreplins et al 2018). Although a lack of scientific consensus persists on what makes a dingo a dingo, and, indeed, whether it matters, here, for simplicity, we consider all wild-living dogs as a single group in Australia (including dingoes, feral dogs and their hybrids), and refer to them hereafter as dingoes, unless stated otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Pet cats, housebound cats, domestic cats, stray cats, colony cats, feral cats, semi-feral cats, community cats, unowned cats and semi-owned cats are common examples (but ironically not clowder). The language chosen reflects human values and interests, and so the names themselves are not neutral but carry an emotional charge that can influence study design, reporting and reception, as noted in work on dogs [8]. In the case of cats, the language may colour perceptions and management options [9,10].…”
Section: What To Call a Cat?mentioning
confidence: 99%
“…Until the name combination Canis dingo was firmly encouraged by Crowther et al (2014), this name was not in common usage and had not been for some 20 years as names such as Canis familiaris dingo or Canis lupus dingo were the most commonly used names for Dingoes. Indeed, a review of 387 papers that used scientific names (Kreplins et al 2018) indicated the most commonly used names were: those including a domestic dog ancestry-Canis familiaris, Canis familiaris dingo, Canis lupus domesticus and C. l. familiaris (169); those referring to a wolf ancestry, as Canis lupus and Canis lupus dingo (154), with only 64 referring to the Dingo as a distinct species (Canis dingo), most of which were published since 2014. Therefore, it could be argued that the attempt to elevate the Dingo to species rank as Canis dingo has added further nomenclatural instability.…”
Section: Namesmentioning
confidence: 99%